Metatranscriptomes reveal functional variation in diatom communities from the Antarctic Peninsula - Pearson, Gareth A (ISME J, 2015)
Functional genomics of diatom-dominated communities from the Antarctic Peninsula was studied using comparative metatranscriptomics. Samples obtained from diatom-rich communities in the Bransfield Strait, the western Weddell Sea and sea ice in the Bellingshausen Sea/Wilkins Ice Shelf yielded more than 500K pyrosequencing reads that were combined to produce a global metatranscriptome assembly. Multi-gene phylogenies recovered three distinct communities, and diatom-assigned contigs further indicated little read-sharing between communities, validating an assembly-based annotation and analysis approach. Although functional analysis recovered a core of abundant shared annotations that were expressed across the three diatom communities, over 40% of annotations (but accounting for <10% of sequences) were community-specific. The two pelagic communities differed in their expression of N-metabolism and acquisition genes, which was almost absent in post-bloom conditions in the Weddell Sea community, while enrichment of transporters for ammonia and urea in Bransfield Strait diatoms suggests a physiological stance towards acquisition of reduced N-sources. The depletion of carbohydrate and energy metabolism pathways in sea ice relative to pelagic communities, together with increased light energy dissipation (via LHCSR proteins), photorespiration, and NO(3)(−) uptake and utilization all pointed to irradiance stress and/or inorganic carbon limitation within sea ice. Ice-binding proteins and cold-shock transcription factors were also enriched in sea ice diatoms. Surprisingly, the abundance of gene transcripts for the translational machinery tracked decreasing environmental temperature across only a 4 °C range, possibly reflecting constraints on translational efficiency and protein production in cold environments.